Low occurrence and clonal relatedness of multi-drug resistant Escherichia coli carrying transmissible colistin resistance mcr-1 genes in Ugandan poultry - Wainaina, Martin; Ndoboli, Dickson; Ayebare, Dreck; Mbatidde, Irene; Roesel, Kristina; Hammerl, Jens Andre; Moodley, Arshnee; Tenhagen, Bernd-Alois; Binsker, Ulrike (Frontiers in Veterinary Science, 2025)
IntroductionColistin resistance is an emerging global health concern that can lead to limited treatment options for life-threatening human infections. Colistin has widespread use in agriculture in many countries to boost livestock health and productivity. Mobile colistin resistance (mcr) genes have been reported globally and facilitate the spread of colistin resistance, but there is limited data on their occurrence in Uganda. This study aimed to identify and characterise mcr-carrying Escherichia coli from semi-intensive and free-ranging poultry farms in Uganda.Methodsmcr-carrying E. coli were isolated and characterised from 402 poultry farms in Wakiso and Soroti districts of Uganda using a combination of selective isolation, PCR detection, antimicrobial susceptibility testing, plasmid transfer assays and next generation sequencing.ResultsFive E. coli isolates from five farms (1.2%) were positive for mcr-1 located on transmissible IncI2(Delta) plasmids of ~63 kb. All isolates had MIC values ranging from 4 to 8 mg/L, belonged to sequence type 155 and exhibited multidrug resistance to antibiotics commonly used on the farms. Whole genome sequencing based phylogeny indicated a close clonal relationship, with SNP distances ranging from 0 to 4 between the isolates from both districts. Lastly, the plasmids were transmissible with a transfer frequency of ~1 × 10−6 transconjugants per donor bacteria.ConclusionWe report mcr genes in Ugandan poultry for the first time. Although our study focused solely on poultry farms and revealed a low mcr gene occurrence, it highlights the need for attention. Regular One Health monitoring of colistin use and resistance is important to mitigate possible bacterial selection and spread. Policy interventions should focus on promoting the prudent use of antimicrobials in livestock production, and improving biosecurity measures on farms.